Research on the development strategy of telemetry systems based on the SWOT-AHP model analysis - HE Rong, ZENG Dexian, WANG Wanli, GAO Junxing, YANG Kuan, WANG Zhitao (Zhihui kongzhi yu fangzhen)
In order to explore the future development strategy of telemetry system, a research on the development strategy of telemetry system is conducted based on the SWOT-AHP model. Firstly, based on the structural characteristics and functional attributes of the telemetry system, the advantages, disadvantages, opportunities and challenges of the telemetry system, the qualitative and quantitative analysis provides the optimal development strategy. The results show that the telemetry system development priorities the SO strategy, and thus formulates the long-term plan of the telemetry system development strategy, so as to provide a reference for the upgrading and transformation and frontier deployment of the telemetry system.